ANALYSIS OF FACTORS INFLUENCING THE PERFORMANCE OF COMMITMENT MAKING OFFICIALS IN CONSTRUCTION PROJECTS IN THE AGAM DISTRICT REGIONAL GOVERNMENT ENVIRONMENT - Rahmi, Olitia; Zaidir, Zaidir; BQS, Wahyudi P Utama (Rang Teknik Journal, 2024)
The increase in the budget allocation for procurement of goods or services in the Agam Regency Government cannot be separated from the problem of procurement of goods or services. In Agam Regency, the problem that often arises in the appointment of commitment making officials is limited human resources in managing construction work so that many projects are found to be late in completing their work. The aim of the research is to identify factors and determine the most dominant factors that influence commitment making officials performance in construction projects in Agam Regency, and create a measurement model for the relationship between commitment making officials performance. The research method used is a quantitative research method, namely by distributing questionnaires to respondents. The results of the research conducted show factors that influence commitment making officials performance in construction projects in Agam Regency, namely the Technical Capability and Workload factors, the Capability factors in planning and control, the Knowledge and Budget Factors and the Skills Factors